2018
DOI: 10.3168/jds.2017-13746
|View full text |Cite
|
Sign up to set email alerts
|

Association of paratuberculosis sero-status with milk production and somatic cell counts across 5 lactations, using multilevel mixed models, in dairy cows

Abstract: The aim of this work was to investigate associations between individual cow Mycobacterium avium ssp. paratuberculosis (MAP) seropositivity, 305-d corrected milk production, and somatic cell count during 5 lactations lifespan in Portuguese dairy herds using multilevel mixed models. We used MAP serum ELISA (Idexx MAP Ac, Idexx Laboratories Inc., Westbrook, ME) results (n = 23,960) from all the 20,221 adult cows present in 329 farms and corresponding 47,586 lactation records from the National Dairy Improvement As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…In the same study, mastitis was more likely in high-risk cows compared to their medium-or low-risk herdmates. In a large Portuguese study, MAP serum ELISA positive cows had elevated SCC levels, and the difference between test positive and negative cows increased in higher parities (27). Other studies found no difference in SCC between test positive and negative cows, using fecal culture (14) or serum ELISA (19).…”
Section: Milk Production Composition and Sccmentioning
confidence: 89%
See 1 more Smart Citation
“…In the same study, mastitis was more likely in high-risk cows compared to their medium-or low-risk herdmates. In a large Portuguese study, MAP serum ELISA positive cows had elevated SCC levels, and the difference between test positive and negative cows increased in higher parities (27). Other studies found no difference in SCC between test positive and negative cows, using fecal culture (14) or serum ELISA (19).…”
Section: Milk Production Composition and Sccmentioning
confidence: 89%
“…Tiwari et al (26) detected an association between MAP and lower milk yield only from the fourth lactation onwards. Martins et al (27) proposed that serum MAP ELISA positive cows had 0.4-0.6 kg/day higher milk yield in the first lactation, suggesting that increased milk production capacity may be related to susceptibility to MAP infection. In the same study, milk losses amounted to 0.2, 0.8, 1.5, and 2.1 kg/day from the second to fifth lactation, respectively, leading to an accumulated loss of nearly 1,300 kg in the first five lactations in ELISA positive cows, on average.…”
Section: Milk Production Composition and Sccmentioning
confidence: 99%
“…Numerous studies have reported a reduction in milk production as a result of JD McAloon et al, 2015). A study by Martins et al (2018) investigating milk production across 5 lactations, found that MAP status affected milk yield, with an average loss of 1,284.8 kg of milk from JD positive (at least 1 positive ELISA test result) compared to JD negative cows (all test results were negative). However, JD positive cows had, on average, higher milk production during their first lactation than JD negative cows and it was from the third lactation onwards that the losses were detectable (Martins et al, 2018), although the authors did not report whether the JD positive cows were showing any clinical signs of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although Ott et al (1999) estimates the cost of JD to the US dairy industry as $200 to $250 million annually, calculating economic losses associated with JD is difficult. Infected animals may have an increased risk of other diseases, such as mastitis (Pritchard et al, 2017;Rossi et al, 2017) and milk production is reduced (Martins et al, 2018), so many infected animals may be culled prior to the clinical stages of JD and therefore misclassified (Caldow et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…are left to be controlled by each Member State (MS) [7]. However, these diseases can also cause economic losses, which are usually hidden at first glance, as they often have subclinical or chronic courses [4]. They also reduce the welfare of affected animals [3].…”
Section: Abstract: Bovine Control Programmes Europe Infectious Dismentioning
confidence: 99%